Corona Virus Pandemic: Implication on Biodiversity Conservation - Akinsorotan, Oluseun A.; Olaniyi, Oluwatobi E.; Adeyemi, Ayomide A.; Olasunkanmi, Adeola H. (Frontiers in Water, 2021)
Globally, the Covid-19 pandemic affected the environment, placing a strain on the economy and all parts of human society. The effects of Covid-19 are inevitable, as there is a reduction in human pressures on the natural ecosystem because of the lockdown of social and economic activities. Ecosystem integrity (in terms of species diversity, endemism, and threats) in African countries with global hotspots for biodiversity conservation threatened. This paper provides a snapshot of the quickly growing situation caused by the Covid-19 pandemic lockdown and predicts events during normality. At present, essential conservation work (protected area/national park staff still patrol and guard vulnerable species and landscapes) is still ongoing across the globe with the accruing positive effects of the pandemic - reduced air/water pollution, short-term disruption in wildlife trafficking and ecosystem restoration. Despite this, prevailing problems such as indiscriminate exploitation of wildlife resources, tourism revenue loss, staff absenteeism/poor performance, increased human dependence on natural resources, disruptions of field/research work and species monitoring would persist. The Covid-19 pandemic will affect conservation program funding in most African countries. Our world is changing, and the conservation community must be ready to respond appropriately.